2011
DOI: 10.1210/jc.2010-2532
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Muscle AMPK Activation in the Metabolic Syndrome May Attenuate Improved Insulin Action after Exercise Training

Abstract: Failure of resistance training to improve insulin responsiveness in MS subjects was coincident with diminished phosphorylation of muscle AMPK, but increased phosphorylation of mTOR, suggesting activation of the mTOR pathway could be involved in inhibition of exercise training-related increases in AMPK and its activation and downstream events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 51 publications
4
61
0
Order By: Relevance
“…Together, these data suggest that the presence of IFG in adults with IGT modifies exercise training-induced improvements in glucose regulation. Although exercise generally increases insulin sensitivity in adults across the glucose continuum (11,22,26,35), the data are consistent with carefully controlled studies reporting that people with metabolic syndrome or early-onset type 2 diabetes have less improvement in clamp-derived whole body insulin sensitivity following 12 wk of exercise compared with healthy age, weight, and fitness-matched counterparts (25,30). In addition, the Diabetes Prevention Program Outcomes Study emphasized recently that adults with more severe forms of prediabetes were least likely to regress to normal glucose tolerance (37).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Together, these data suggest that the presence of IFG in adults with IGT modifies exercise training-induced improvements in glucose regulation. Although exercise generally increases insulin sensitivity in adults across the glucose continuum (11,22,26,35), the data are consistent with carefully controlled studies reporting that people with metabolic syndrome or early-onset type 2 diabetes have less improvement in clamp-derived whole body insulin sensitivity following 12 wk of exercise compared with healthy age, weight, and fitness-matched counterparts (25,30). In addition, the Diabetes Prevention Program Outcomes Study emphasized recently that adults with more severe forms of prediabetes were least likely to regress to normal glucose tolerance (37).…”
Section: Discussionsupporting
confidence: 76%
“…However, given that in vivo (29,42) and in vitro studies (3) report that chronic hyperglycemia overloads mitochondrial oxidative capacity, it appears plausible that exercising with a background of hyperglycemia impairs skeletal muscle glucose uptake through a metabolic stress/inflammatory-related pathway (36). This hypothesis is consistent with evidence that PGC-1␣ and AMPK expression are lower after exercise in insulin-resistant individuals (13,24,30).…”
Section: Discussionmentioning
confidence: 61%
“…This highlights the fact that the results of studies investigating the effects of exercise interventions on insulin sensitivity have been conflicting. Whereas some studies have reported greater benefits of exercise in people with poorer baseline insulin sensitivity (Jenkins & Hagberg, 2011), others have reported impaired responses to exercise in patients with T2D or metabolic syndrome (Layne et al, 2011;Sriwijitkamol et al, 2007), and longer T2D disease duration is associated with poorer improvements in insulin sensitivity and glycaemic control following aerobic exercise training (Solomon et al, 2013). In addition, it has been suggested that low response to exercise for important risk factors such as V O2max or insulin sensitivity may result in increased risk of developing cardiometabolic disease (Lessard et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are conflicting data on whether patients with T2D will have enhanced (Jenkins & Hagberg, 2011), or impaired (Layne et al, 2011;Sriwijitkamol et al, 2007) responses to exercise training in general, and therefore it remains unknown whether cyclingbased REHIT can be used to improve insulin sensitivity and V O2max in T2D patients, and whether it may be effective at improving other important health markers such as blood pressure, blood lipid profile, and body composition. Moreover, in order for any intervention to be recommended to patients with T2D, the effects of the intervention should be at least as good as those associated with current physical activity recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the authors found nondiabetic subjects with the metabolic syndrome had muscle fiber composition very similar to that seen in type 2 diabetes (9). This study was performed to determine whether the muscle fiber composition of metabolic syndrome subjects correlated with measures of insulin resistance.…”
mentioning
confidence: 94%